PENGEMBANGAN MATERI AJAR FPB BERBASIS PMRI DI SEKOLAH DASAR - Ika Syafrina; Syahrilfuddin Syahrilfuddin; Jesi Alexander Alim (Jurusan Ilmu Pendidikan, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Riau, 2022)
This study aims to produce products for developing PMRI-based GCD teaching materials in elementary schools that are in accordance with valid and practical characteristics. In this research used the RnD method with Plomp model. The stages of development carried out are the Preliminary Research Phase, Prototyping Phase, and Assessment Phase. The teaching materials developed by the researchers were validated by 3 experts consisting of material experts, educational technology experts and linguists. For practicality, it can be seen from the practicality questionnaire of teachers and students given by during the small group trial. Data collection techniques carried out by interviews, observations, and questionnaires. The data obtained from the data collection is then processed by quantitative analysis techniques and descriptions. Based on the results of the validation of the teaching materials developed, the criteria are valid (feasible) with an average percentage of 93.75%. The practicality of teaching materials based on the teacher's practicality questionnaire is 90.62% with very practical criteria, and based on the students' practicality questionnaire is 81.04% with practical criteria. Based on the results it can be concluded that the PMRI-based GCD teaching materials in elementary schools have valid and practical criteria, which means that they can be used in learning.